PENGARUH MODEL PEMBELAJARAN VCT TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DIKELAS III PADA PEMBELAJARAN PKN DI MI - Aulia Rahmadani Nasution; Zurriaty; Sarah Fazilla (STKIP Subang, 2026)
This study aimed to determine the implementation of Civic Education (PKn) learning before and after the application of the Value Clarification Technique (VCT) learning model and its effect on the critical thinking skills of third-grade students at MIN 03 Lhokseumawe City. The study was motivated by the low level of students’ critical thinking skills, as reflected in their limited ability to analyze problems, express opinions, and make decisions during the learning process. To address this issue, the VCT model was implemented to encourage students to actively explore, clarify, and apply values in learning activities. This research employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 60 third-grade students divided into an experimental class and a control class, each comprising 30 students. Data were collected through pretests and posttests and analyzed using normality, homogeneity, and hypothesis tests. The findings indicated that the implementation of PKn learning improved after the application of the VCT model. Before the intervention, learning activities were predominantly teacher-centered, resulting in limited student participation. After the implementation of VCT, students became more actively engaged in discussions, value clarification, and reflective decision-making. The experimental class achieved a higher posttest mean score (82.33) compared to the control class (79.33). These results demonstrate that the VCT learning model positively contributes to the development of students’ critical thinking skills in Civic Education learning.